The interaction network of the GroEL chaperonin - Hartl, F. Ulrich (Henry Stewart Talks, 2012)
De novo protein folding and proteome maintenance critically depend on molecular chaperones, Transitions during protein folding, Chaperone assisted protein folding, Productive protein folding is often competed by aggregation, Reconstitution of GroEL-assisted folding, GroEL and GroES function as a folding cage for proteins up to 60 kDa, GroEL structure, Which proteins need GroEL/GroES for folding?, Identification of the GroEL interaction proteome, Class III substrates are of relatively low cellular abundance but occupy most of the GroEL capacity, Chaperonins provide a specialized folding environment with two functional elements: sequestration and steric confinement in a hydrophilic cage, GroEL as part of the cytosolic chaperone network
Reviewed at 2021/09/15